Metabolic and transcriptional aspects of Capsicum chinense fruits in different developmental stages - Salvador, Acácio Rodrigues (2021)
The Capsicum genus is highly phenotypically diverse and considered nonclimacteric. Although some studies with nonclimacteric fruits have already been carried out, knowledge about the regulation between transcripts and metabolites is still scarce. We selected phenotypically contrasting Capsicum chinense accessions and analyzed in detail the metabolism in placenta and pericarp fruit and performed a transcripts profile to identify possible relationships between metabolism and gene expression. We quantified and analyzed primary metabolites, capsaicin, phenols, proteins, total amino acids, sugars and starch in three stages of development (20, 45 and 60 days after anthesis) and identified 16803 genes expressed from different functional classes and correlated with 69 metabolites quantified in two stages of development (20 and 60 days after anthesis). Our results suggest that most of the observed metabolic variability is between the stages of fruit development and not between accessions. In addition, we show that pungency, determined by the metabolism of the placenta, significantly interferes with the metabolism of the fruit. The integration of the transcript and metabolite profile through multivariate analysis provides several correlations between the metabolic and transcript classes that can be studied in detail in future research. Our results suggest that there is a complex control during fruit development that determines phenotypic characteristics, in addition, our data increase our knowledge about the regulation of TSS accumulation in nonclimacteric fruits. Keywords: Capsaicin. Primary metabolites. Fruits. Transcriptome.